Cybele's secret - Marillier, Juliet (New York : Knopf, 2008)
Scholarly eighteen-year-old Paula and her merchant father journey from Transylvania to Istanbul to buy an ancient pagan artifact rumored to be charmed; but others, including a handsome Portuguese pirate and an envoy from the magical Wildwood, want to acquire the item as well.
"A companion novel to Wildwood dancing"--Cover.
Booklist starred.
Kirkus Review.
Young Adult
Keywords: Antiquities -- Juvenile fiction; Cults -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Magic -- Juvenile fiction; Merchants -- Juvenile fiction; Pirates -- Juvenile fiction; Sisters -- Juvenile fiction; Supernatural -- Juvenile fiction; Antiquities -- Fiction; Brothers and sisters -- Fiction; Cults -- Fiction; Fathers and daughters -- Fiction; Magic -- Fiction; Merchants -- Fiction; Pirates -- Fiction; Supernatural -- Fiction; Antiquities -- Fiction; Cults -- Fiction; Father-daughter relationship -- Fiction; Magic -- Fiction; Merchants -- Fiction; Pirates -- Fiction; Sisters -- Fiction; Supernatural -- Fiction; Istanbul (Turkey) -- History -- Juvenile fiction; Turkey -- History -- Juvenile fiction; Istanbul (Turkey) -- Fiction; Turkey -- Fiction; Istanbul (Turkey) -- Fiction; Turkey -- Fiction